2001
DOI: 10.1086/321851
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on Animal Models: Chronic Intracellular Infections

Abstract: Systemic human disease caused by organisms of the Mycobacterium avium-Mycobacterium intracellulare complex (MAC) represent a chronic intracellular infection in human hosts who are usually immunocompromised. To develop improved treatment and prophylaxis, and to obtain a better understanding of pathogenesis, we studied the beige mouse (C57 beige(+)/beige(+)) challenged orally or intravenously with a human isolate that causes lethal disease in patients with AIDS (MAC 101, serovar 1). Encouraging anti-MAC studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…A MAC-infected C3HeB/FeJ mouse model is supported by other murine studies showing early in vivo expression of IFN-γ during MAC - infection correlated with resistance to the infection (Gangadharam, 1995; Young and Bermudez, 2001; Appelberg, 2006). The use of specific neutralizing antibodies in vivo led to the identification of IFN-γ and TNF-α as protective cytokines acting at the effector level of resistance to MAC (Gangadharam, 1995; Young and Bermudez, 2001; Appelberg, 2006).…”
Section: Discussionmentioning
confidence: 59%
“…A MAC-infected C3HeB/FeJ mouse model is supported by other murine studies showing early in vivo expression of IFN-γ during MAC - infection correlated with resistance to the infection (Gangadharam, 1995; Young and Bermudez, 2001; Appelberg, 2006). The use of specific neutralizing antibodies in vivo led to the identification of IFN-γ and TNF-α as protective cytokines acting at the effector level of resistance to MAC (Gangadharam, 1995; Young and Bermudez, 2001; Appelberg, 2006).…”
Section: Discussionmentioning
confidence: 59%
“…The stomach was traditionally thought to be a barrier to mycobacteria, but it was shown that virulent M. avium strains could infect mice orally and be found in gut lymphoid tissues [21,22]. If the beige mutant in the C57BL/6 mouse was used, this was amplified [21,22]. Our laboratory has also found that SCID mice infected orally with M. abscessus resulted in a progressive infection (Ordway D et al, [18] unpublished observations).…”
Section: Routes Of Infection In Animal Modelsmentioning
confidence: 99%
“…The stomach was traditionally thought to be a barrier to mycobacteria, but it was shown that virulent M. avium strains could infect mice orally and be found in gut lymphoid tissues [21,22]. If the beige mutant in the C57BL/6 mouse was used, this was amplified [21,22].…”
Section: Routes Of Infection In Animal Modelsmentioning
confidence: 99%
“…However, if beige mice with C57BL/6 background were used, the degree of infection was further increased [68,69]. Additional studies showed that M. avium accessed the gut epithelium by interactions with enterocytes [69].…”
Section: Evidence For Ntm Interference With Bcg Efficacymentioning
confidence: 99%